Climate adaptation in the Indu-Gangetic Basin - Amarasinghe, Upali A.; Sikka, Alok; Surinadu, L. (Edward Elgar Publishing, 2022)
Indus and Ganga Basins (IGB), which spread over 220 million ha and with over one billion population, grapples with multiple risks. Climate change will exacerbate the water-related recurrent disasters of floods and droughts. Variability and extreme events of rainfall and temperature are increasing. Monsoon rains in four months from June to September bring 80% of the total rainfall. Irrigation is critical, especially for dry-season agriculture and for livelihoods and food security. Groundwater depletion, water quality, and environmental issues reached critical points threatening sustainable agriculture in many locations. This paper focuses on innovative water-related adaptation strategies being pilot tested and implemented to reduce the risks and enhance productivity and resilience in the agriculture sector in the Basins.